The effectiveness of epidural blood patch in patients with cerebral palsy treated with intrathecal baclofen implantation. Issue 2 (14th January 2020) - Imerci, Ahmet; Rogers, Kenneth; Dixit, Divya; McManus, Maura; Miller, Freeman; Sees, Julieanne P.
Abstract: Background: Cerebrospinal fluid leak and postdural puncture spinal headache following intrathecal baclofen therapy are known complications. Although primary treatments are conservative, epidural blood patch is an alternative in patients with persistent and severe symptoms. Aim: The purpose of this article is to review the effectiveness of epidural blood patch for the treatment of spinal headache and cerebrospinal fluid leak associated with intrathecal baclofen treatment in children with cerebral palsy. Methods: Our database was reviewed for epidural blood patch in 341 pediatric patients with cerebral palsy who underwent primary intrathecal baclofen treatment from 2004 to 2018 at one institution. The number of patches, time frame of treatment, and effectiveness of the epidural blood patch were collected. All patients treated with epidural blood patch were evaluated for primary and secondary intrathecal baclofen‐related procedures, and subsequent treatment of intrathecal baclofen associated with cerebrospinal fluid leak and spinal headache. Results: Twenty‐nine epidural blood patch procedures were performed on 26 patients who had received intrathecal baclofen procedures. Of these 26 patients, four had a secondary epidural blood patch. The incidence of spinal headache/cerebrospinal fluid leak was 31% (107/341), and 81/107 (76%) patients with spinal headache/cerebrospinal fluid leak responded to conservative treatments. Success rate for initial epidural blood patch was 79.3% (23/29). The second epidural blood patch was performed in four patients after failure of initial epidural blood patch. Second epidural blood patch success rate was 75% (3/4). Conclusion: Spinal headache and cerebrospinal fluid leak are known complications after intrathecal baclofen treatment in children with cerebral palsy. When conservative treatments are unsuccessful, epidural blood patch can be used with confidence for these patients. In patients with ongoing symptoms, it is possible to obtain success by repeating the epidural blood patch to continue intrathecal baclofen treatment and avoid aggressive surgery.